Sustainable Oral Healthcare from Ethical Standpoint - Kadioglu, Funda Gülay (Acta Bioethica, 2025)
Sustainability refers to the efficient and balanced use of resources, considering the needs of future generations. Sustainable development and sustainability address the most significant and complex challenges humanity has ever faced. Sustainable healthcare systems consider the long-term social and environmental impacts of health services, utilizing existing resources effectively, and concurrently addressing the health rights of the population. The key components of such systems include reducing, recycling, and reusing medical waste, energy efficiency, minimally invasive practices, and reduced carbon footprint by eco-friendly principles. Oral healthcare, integral to overall well-being, must align with sustainability. Ethical delivery of oral healthcare demands a delicate balance between current patient needs and preserving resources for future generations. Professionals in the field increasingly recognize the imperative to minimize environmental footprints while upholding standards of care. Eco-friendly dentistry emphasizes waste reduction, energy conservation, and the adoption of innovative, sustainable materials and practices. Environmental ethics underscore the interconnectedness of human health and environmental well-being. They advocate for strategies to mitigate environmental health risks and promote sustainable practices in oral healthcare. By embracing sustainability, oral healthcare professionals contribute to a healthier planet and ensure the longevity of their practice for generations to come.